The art of learning : neural networks and education - Yu, Francis T. S., 1932-; Yu, Edward H.; Yu, Ann G. (Boca Raton, FL : CRC Press Taylor & Francis Group, 2019)
'This book has 15 sections. It starts with the common sense on education and moves on to the neural network operation. The art of learning, associative, cognitive, and creative learning are stated and defined. Learning simplicity, information content as related to neural network learning are discussed. Additionally, the author discusses neural plasticity and adaptability in smarter neural networks. If we know our human brain's basic abilities and limitation then a better educational methods can be implemented'--
Common sense training -- Audio vs visual learning -- Human brain vs computer -- Simplicity in learning -- Memory tricks -- Talent -- Curiosity & discovery -- Unsupervised learning -- Mistakes -- Questions -- Approximation -- Every problem has multiple solutions -- Illusion of mastery -- Late bloomers -- Leadership in education.
Includes bibliographical references.
Keywords: Learning -- Physiological aspects; Cognitive learning; Paired-association learning